Implementasi Kebijakan Perijinan Investasi di Daerah Kabupaten dan Kota di Indonesia ditinjau Berdasarkan Prinsip Good Local Governance - Iriani, Enni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2008)
Private Investment in one of the ways the government taken to recover from the last monetary crisis. The related efforts, however, slow down due to complicated problems in public services. Hence, in year 2006, the Government issued the Presidential Decree No.3/2006 on Policy Package for Enhancing Investment Climate. It is believed to be the starting point of public service reform programs. Prior to that, several policies have already been delivered, such as the Public Affair Ministerial Decree No. 25/1998 on One Roof Service. The goal of both policies is to improve public service deliveries to become as fast, cheap, right, and accountable as possible in accordance with those principles to be fulfilled so as to create good local governance. Yet, so far the public service is still the existing issue in enhancing investment in Kabupaten/Kota in Indonesia and it is assumed, owing to the negligence towards the GLG principles. In the light of the phenomenon, the study was conducted to formulate strategic recommendation and action plan for the implementation of GLG principles in public services reform. This article sums up the study which reveals some facts on: 1) the efforts taken by Regional Government in reforming public service, 2) the quality of public service in Kabupaten/Kota, 3) the implementation of GLG principles in public service delivery, and 4) the policy recommendation and action plan for implementinng GLG principles.